LEVEL TEKNOLOGI, FOREIGN OWNERSHIP, DAN IMPLEMENTASI INTERNET FINANCIAL REPORTING - Setiawan, Antonius Singgih; Michael, Michael (Universitas Pendidikan Indonesia, 2020)
The progress of internet-based communication technology has influenced the pattern of information delivery in the business world. Internet Financial Reporting (IFR) has become a medium of communication between companies and investors in delivering company financial reporting information. For this reason, this research is needed to identify what factors can influence IFR implementation at the Indonesian public company. This study aims to identify whether the level of technology and foreign ownership can affect IFR implementation in public companies in Indonesia. A total of 87 public company samples were used to test the research hypothesis. Research data were analyzed using multiple regression models. The results found indications that the level of company technology has a positive influence on the implementation of IFR in public companies in Indonesia. However, foreign ownership does not provide an effect for IFR implementation in public companies in Indonesia.